2005
DOI: 10.1590/s1020-49892005000400005
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes in Puerto Rico concerning dengue prevention

Abstract: The patterns of knowledge and opinion that emerged in the discussions can be arranged along an axis going from high levels of correct knowledge to low levels of correct knowledge about dengue and dengue hemorrhagic fever and related practices. There were few participants at either extreme. Three themes explained these patterns: misconceptions about dengue (based on previously delivered information), the "invisibility" of dengue (as compared to other diseases), and responsibility (individual and Government). Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 10 publications
6
52
0
2
Order By: Relevance
“…The percentage of positive cases having headache, eye pain and vomiting were significantly higher during the acute phase of the illness than that in the negative cases. These common clinical features in typical dengue infection were also observed in other published studies (Pérez-Guerra et al, 2005;Chuang et al, 2008;Lee et al, 2012). Our laboratory data showed that the percentage of dengue patients with mean elevated level of Aspartate transaminase and Alanine transaminase were significantly higher than that of laboratory dengue negative patients.…”
Section: Journal Of Virology and Microbiologysupporting
confidence: 89%
“…The percentage of positive cases having headache, eye pain and vomiting were significantly higher during the acute phase of the illness than that in the negative cases. These common clinical features in typical dengue infection were also observed in other published studies (Pérez-Guerra et al, 2005;Chuang et al, 2008;Lee et al, 2012). Our laboratory data showed that the percentage of dengue patients with mean elevated level of Aspartate transaminase and Alanine transaminase were significantly higher than that of laboratory dengue negative patients.…”
Section: Journal Of Virology and Microbiologysupporting
confidence: 89%
“…This behaviour suggests that the concept of a community approach to mosquito control is, in fact, not a reality. Perez-Guerra et al [35] also found this behavioural characteristic in Puerto Rico where individuals often blamed their neighbours for not contributing appropriately and neglecting the combined efforts necessary for successful community based programmes. In Sint Eustatius, it may be a strategic option for the Public Health Department to focus on the household level rather than the community and build collaborations with households by supporting them when they actively practise mosquito control.…”
Section: Discussionmentioning
confidence: 92%
“…The significance of prevention and control may be attributed to the 2014 Chikungunya outbreak resulting in the Sint Eustatius population actually experiencing a mosquito-borne disease. In Puerto Rico, Perez et al [35,36] found that residents considered dengue an issue within the community mainly when people were aware of cases within the population.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies conducted with Puerto Rican residents found that a perceived link between flu-like illness and dengue has existed in the past due to the similarities of early disease symptoms. 8,9 In 2010, an island-wide educational campaign was launched to promote dengue prevention practices and encourage people to get the H1N1 vaccine. Juxtaposition of the perceived side effects from influenza vaccination and the message delivered by the educational campaign could have created more confusion among the public because they might have thought that the H1N1 vaccine protected against dengue.…”
Section: Discussionmentioning
confidence: 99%
“…7 Although community-based education programs have increased knowledge about vector control among the public, these programs have had limited success in changing behavior to prevent or control endemic dengue. 8,9 Studies in various countries have shown that use of pesticides has had little effect on reducing vector populations of Aedes aegypti. 7 Given the lack of effective tools for the primary prevention of dengue, there has been a major effort to develop safe and effective dengue vaccines as a tool to prevent this disease.…”
Section: Introductionmentioning
confidence: 99%